2016
DOI: 10.1111/jpc.13268
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and behavioural factors associated with school children's sleep in Aotearoa/New Zealand

Abstract: It is important to consider children's sleep within the wider family context and to be aware that parents may over-estimate their children's sleep. Simple strategies to promote sleep health in clinical settings or education programmes include regular weekend bedtimes that align with those on school nights, removing technology from bedrooms and minimising caffeine consumption. An awareness of potential sleep differences associated with shift-working adults may ensure children are supported to have consistent sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 32 publications
2
9
0
Order By: Relevance
“…Results show a clear reduction in EPTB (RR 0.61, 95% CI 0.46 to 0.81; 9 randomised controlled trials (RCTs); n=4351) for supplementation compared with placebo. 19 Our DOMInO trial supports the safety data from previous systematic reviews; however, there were more post-term births requiring obstetric intervention (induction or caesarean section) in the ω-3 LCPUFA supplemented group compared with control (17.59% vs 13.72%, adjusted RR 1.28, 95% CI 1.06 to 1.54, p=0.01). To determine both efficacy and safety of this intervention, we therefore plan to undertake a further trial with adequate power to assess the effect of ω-3 LCPUFA supplementation in pregnancy on EPTB as the primary outcome, with a unique design ceasing the intervention at 34 weeks’ gestation to reduce the risk of post-term birth.…”
Section: Introductionsupporting
confidence: 83%
“…Results show a clear reduction in EPTB (RR 0.61, 95% CI 0.46 to 0.81; 9 randomised controlled trials (RCTs); n=4351) for supplementation compared with placebo. 19 Our DOMInO trial supports the safety data from previous systematic reviews; however, there were more post-term births requiring obstetric intervention (induction or caesarean section) in the ω-3 LCPUFA supplemented group compared with control (17.59% vs 13.72%, adjusted RR 1.28, 95% CI 1.06 to 1.54, p=0.01). To determine both efficacy and safety of this intervention, we therefore plan to undertake a further trial with adequate power to assess the effect of ω-3 LCPUFA supplementation in pregnancy on EPTB as the primary outcome, with a unique design ceasing the intervention at 34 weeks’ gestation to reduce the risk of post-term birth.…”
Section: Introductionsupporting
confidence: 83%
“…Of the four studies considering media and actigraph-measured sleep in children, three are in large samples but subject to methodological limitations, including reliance on 1 night of actigraphy (Nixon et al, 2008), use of waist-worn actigraphs (Chaput et al, 2014), and dichotomization of screen time (Harrex et al, 2018). Several studies found no associations between weekly or daily screen time and sleep (e.g., Harrex et al, 2018;Nixon et al, 2008), whereas two other studies found associations between daily screen time and efficiency (but not duration; Chaput et al, 2014) and later bedtimes and shorter sleep duration (Muller, Signal, Elder, & Gander, 2017). Different measurement and outcomes complicate interpretation, but the finding in two studies (Chaput et al, 2014;Muller et al, 2017) that screens in children's bedrooms were related to objective sleep when average daily media use was not suggests that media use is a better predictor near bedtime than across the day, consistent with associations between subjective sleep and prebedtime media use (Hale et al, 2018;Owens et al, 1999).…”
Section: Sleep and Media Usementioning
confidence: 99%
“…Parents completed the Children's Sleep Habits Questionnaire (CSHQ), a screening tool for behavioural and medical sleep problems that has been used in samples from New Zealand, with some modifications to the language used for the appropriateness to local culture. Items on the CSHQ pertain to children's bedtime and bedtime routine, sleep behaviour, waking during the night, morning waking and daytime sleepiness. We used abbreviated scoring procedures, and report a combined score across 33 items, with possible scores ranging from 0 to 66.…”
Section: Methodsmentioning
confidence: 99%